High-Density Polyethylene/SrAl2O4:Eu2+, Dy3+ Photoluminescent Pigments: Material Design, Melt Processing, and Characterization. Issue 4 (4th March 2017) - Barletta, M.; Puopolo, M.; Trovalusci, F.; Vesco, S.
ABSTRACT: High-density polyethylene is a thermoplastic polymer which is extensively involved in the manufacturing of plastic components by injection or blow molding in several industrial domains. Among others, high-density polyethylene is the ideal candidate for the fabrication of indoor and outdoor furniture and general plastic items. In this respect, photoluminescence might be of great relevance as it can replace or support conventional lighting systems in pathway markers and safety signs. In this framework, photoluminescent high-density polyethylene was achieved by the dispersion of SrAl2 O4 :Eu 2+, Dy 3+ functional pigments by twin-screw extrusion. The resulting compound was, subsequently, injection molded to form flat substrates. Characterization of the mechanical properties of the photoluminescent plastic substrates was performed by instrumented flat and scratch indentation as well as by dry sliding linear reciprocating tribological tests. Photoluminescence of the substrates was evaluated by digital imaging technique and quantitative measurements of the emission spectra. Experimental findings state that highly performant and enduring photoluminescent plastics can be achieved by compounding high-density polyethylene with SrAl2 O4 :Eu 2+, Dy 3+ photoluminescent pigments. Injection molding of the engineered material can lead to plastic items characterized by good mechanical performance and reliable photoluminescent emission over a reasonable time range. GRAPHICAL ABSTRACT: